Biofertilizers and biopesticides in sustainable agriculture - Kaushik, B. D.; Kumar, Deepak (Research scientist); Shamim, Md., 1985- (Oakville, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2019)
"This new volume, Biofertilizers and Biopesticides in Sustainable Agriculture, presents strategies for the management of soil and crop diseases. Microbes have attracted worldwide attention due to their role in disease management and remediation of polluted soils. Taking a sustainable approach, this book explores the means of integrating various microbial management approaches to achieve the desired levels of crop yield under both conventional soils and neglected soils through the use of biopesticides and other botanicals as well as biomolecules. This book also presents a broad and updated view of molecular nitrogen fixation and phosphate-solubilizing and sulfur-transforming microbes for nutrition of crops in relation to the role of metal tolerant microbes in providing protection to plants grown in metal-contaminated soils. The preparation and application of biofertilizers, utilization of household waste materials, and use of genetically modified microorganisms (GMOs) in plant growth and development are also well discussed in the volume. The book further describes the functional diversity of plant growth-promotion activity of rhizobacteria, use of vesicular arbuscular mycorrhizal fungi, and utilization of microbial resources for availability of micronutrients (Fe and Zn) as well as secondary nutrients (namely sulfur). The role of fertile soil in crop improvement is highlighted to understand the impact of various management practices on variability of microbes and their functions. In this volume, scientific researchers involve multidisciplinary approaches to understand the complexity and practical utility of the wide spectrum of microbes for the benefit of crops and present valuable research work that explores the role of microbes in crop improvement. This compilation will be very useful and valuable not only for students, teachers, and researchers but also for those interested in microbiology, biotechnology, physiology of plant growth and development, phytoprotection, agronomy, and environmental sciences. Key features: Presents strategies for the management of soil and crop diseases Integrates various microbial management approaches to viral and insect pests and improved crop yield; Presents a new view of molecular nitrogen fixation and phosphate-solubilizing and sulfur-transforming microbes for nutrition of crops; Describes the functional diversity of plant growth-promotion activity and the utilization of microbial resources; Highlights the impact of various management practices on variability of microbes and their functions"--
OCLC-licensed vendor bibliographic record.
Keywords: Biofertilizers; Natural pesticides; Soil management; Field crops -- Diseases and pests -- Control; Sustainable agriculture; SCIENCE / General; SCIENCE / Life Sciences / Biology / Microbiology; TECHNOLOGY / Agriculture / Crop Science